Description and Spatial Modelling of Benthic Communities Distribution in the Canadian Arctic Archipelago - Dumais, Philippe-Olivier; Grant, Cindy; Bluhm, Bodil A.; De Montety, Laure; de Coeli, Lisa Treau; Tremblay, Jean-Éric; Archambault, Philippe (Frontiers in Marine Science, 2022)
In the Arctic, sea ice loss has already transformed the dominant sources and periodicity of primary production in some areas, raising concerns over climate change impacts on benthic communities. Considered to be excellent indicators of environmental changes, benthic invertebrates play important roles in nutrient cycling, sediment oxygenation and decomposition. However, this biological component of the Canadian Arctic Archipelago (CAA) is still somewhat poorly studied compared to other Arctic regions. To partly fill this need, this study aims to evaluate benthic community composition and its relationship to significant environmental drivers and to develop spatial predictive explanatory models of these communities to expand coverage between sampled stations across the Kitikmeot Sea region and Parry Channel. Results from previously collected samples suggest that biodiversity is higher in this region compared to the Beaufort and Baffin Seas, two adjacent regions to the West and East, respectively. This finding leads to the main hypothesis that (1) benthic communities are succeeding one another, forming an ecotone (transition area) between the Beaufort Sea and the Baffin Sea. Other hypotheses are that (2) Pacific Ocean water influence through the CAA can explain part of this gradient, and that (3) terrigenous inputs affect the distribution of species. Overall, results tend to confirm hypotheses. Generalized Linear Models (GLMs) (with R2 up to 0.80) clearly displayed a succession in community distribution from Queen-Maud Gulf (Southwest) to Lancaster Sound (Northeast). Such models can be useful in identifying potential biodiversity hotspots and as a baseline for marine spatial planning purposes. Further, Pacific origin water (traced with concentrations of nitrate relative to phosphate) and terrigenous inputs (traced with silicate concentrations) were related to species and community distribution. Given that these two inputs/factors are generally increasing in the Canadian Arctic, their influence on benthic communities may also be seen to increase in the upcoming years.